2019
DOI: 10.1111/jcmm.14311
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of KDM1A suppresses tumour migration and invasion by epigenetically regulating the TIMP1/MMP9 pathway in papillary thyroid cancer

Abstract: Epigenetic dysregulation plays an important role in cancer. Histone demethylation is a well‐known mechanism of epigenetic regulation that promotes or inhibits tumourigenesis in various malignant tumours. However, the pathogenic role of histone demethylation modifiers in papillary thyroid cancer (PTC), which has a high incidence of early lymphatic metastasis, is largely unknown. Here, we detected the expression of common histone demethylation modifiers and found that the histone H3 lysine 4 (H3K4) and H3 lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…The BRD4 inhibition, by JQ1, which also inhibits c-Myc and induce TTF1 , or by AZD5153, impairs TC cell growth, suggesting that it is critical for thyroid proliferation ( 57 , 58 ). KDM1A is a H3K9 demethylase frequently overexpressed in PTCs and required for migratory and invasive capabilities of PTC cells ( 59 ). TIMP1 has been described as a KDM1A target.…”
Section: Epigenetic Alterations Sustaining Tcscs Origin and Maintenaimentioning
confidence: 99%
See 1 more Smart Citation
“…The BRD4 inhibition, by JQ1, which also inhibits c-Myc and induce TTF1 , or by AZD5153, impairs TC cell growth, suggesting that it is critical for thyroid proliferation ( 57 , 58 ). KDM1A is a H3K9 demethylase frequently overexpressed in PTCs and required for migratory and invasive capabilities of PTC cells ( 59 ). TIMP1 has been described as a KDM1A target.…”
Section: Epigenetic Alterations Sustaining Tcscs Origin and Maintenaimentioning
confidence: 99%
“…TIMP1 has been described as a KDM1A target. KDM1A epigenetically silences TIMP1 and subsequently activates MMP9 promoting metastasis and migration ( 59 ). Finally, the enzymatically active component of the PRC complex, EZH2, involved in the regulation of embryonic development and responsible for the trimethylation of lysine 27 on H3 (H3K27me3), leading to silencing of gene transcription, is overexpressed in ATCs ( 60 ).…”
Section: Epigenetic Alterations Sustaining Tcscs Origin and Maintenaimentioning
confidence: 99%
“…Our study revealed higher KDM1A expression in breast cancer tissue than in normal tissue. High KDM1A expression was associated with aggressive clinical outcomes, such as lymph node involvement, high histological grade, HER2 positivity and lymphatic invasion, which can be found in studies of other cancers [ 35 ]. However, the specific mechanism of how high KDM1A expression affects breast cancer remains poorly understood.…”
Section: Discussionmentioning
confidence: 96%
“…What's more, further luciferase reporter assay con rmed such regulatory relation. MMP9 is a well-kown tumor promotor and mainly enhances the invasion and metastasis of various tumors [27][28][29]. Moreover, MMP9 also participates in regulating tumor growth [30].…”
Section: Discussionmentioning
confidence: 99%